Investigating hypoxia in aquatic environments: diverse approaches to addressing a complex phenomenon. - Boltacheva, Natalya; Mazlumyan, Sofia A (PANGAEA, 2012)
During RV Maria S. Merian 15/1 cruise (April-May 2010). macrobenthos was sampled and distribution on the Black Sea shelf and the upper slope area off the Bosporus Strait outlet area, within the framework of the EU 7th FP project HYPOX (In situ monitoring of oxygen depletion in hypoxic ecosystems of coastal and open seas, and land-locked water bodies) EC Grant 226213
Total macrobenthos abundance during Maria S. Merian cruise MSM15/1 from the target sites of Istanbul Strait (Bosporus outlet), Black Sea
Keywords: BC; Black Sea; Box corer; Counting; Counting >150 µm fraction; Date/Time of event; DEPTH, sediment/rock; HYPOX; In situ monitoring of oxygen depletion in hypoxic ecosystems of coastal and open seas and land-locked water bodies; Macrozoobenthos; Macrozoobenthos, biomass, wet mass; Maria S. Merian; MSM15/1; MSM15/1_231-1; MSM15/1_233-1; MSM15/1_246-1; MSM15/1_247-1; MSM15/1_259-1; MSM15/1_260-1; MSM15/1_278-1; MSM15/1_279-1; MSM15/1_282-1; MSM15/1_293-1; MSM15/1_294-1; MSM15/1_297-1; Number of species